Structure-kinetic relationship reveals the mechanism of selectivity of FAK inhibitors over PYK2. Issue 5 (20th May 2021) - Berger, Benedict-Tilman; Amaral, Marta; Kokh, Daria B.; Nunes-Alves, Ariane; Musil, Djordje; Heinrich, Timo; Schröder, Martin; Neil, Rebecca; Wang, Jing; Navratilova, Iva; Bomke, Joerg; Elkins, Jonathan M.; et al.
Summary: There is increasing evidence of a significant correlation between prolonged drug-target residence time and increased drug efficacy. Here, we report a structural rationale for kinetic selectivity between two closely related kinases: focal adhesion kinase (FAK) and proline-rich tyrosine kinase 2 (PYK2). We found that slowly dissociating FAK inhibitors induce helical structure at the DFG motif of FAK but not PYK2. Binding kinetic data, high-resolution structures and mutagenesis data support the role of hydrophobic interactions of inhibitors with the DFG-helical region, providing a structural rationale for slow dissociation rates from FAK and kinetic selectivity over PYK2. Our experimental data correlate well with computed relative residence times from molecular simulations, supporting a feasible strategy for rationally optimizing ligand residence times. We suggest that the interplay between the protein structural mobility and ligand-induced effects is a key regulator of the kinetic selectivity of inhibitors of FAK versus PYK2. Graphical abstract: Highlights: A helical DFG motif causes slow ligand dissociation rates in FAK but not PYK2 NanoBRET represents a versatile method measuring ligand dissociation rates in cells τRAMD simulation provides a tool for accurate ligand-binding kinetic predictions Abstract : Berger et al. present a rationale for the selectivity of PF-562271 on FAK over PYK2. Investigation of an inhibitor series by structural and biophysical, computational, as well as cellular techniques provided a structure-kinetic-relationship and revealed a ligand-induced helical DFG motif resulting in kinetic selectivity of FAK inhibitors over PYK2.